2015
DOI: 10.1002/mrm.25612
|View full text |Cite
|
Sign up to set email alerts
|

Retrospectively gated intracardiac 4D flow MRI using spiral trajectories

Abstract: Purpose: To develop and evaluate retrospectively gated spiral readout four-dimensional (4D) flow MRI for intracardiac flow analysis. Methods: Retrospectively gated spiral 4D flow MRI was implemented on a 1.5-tesla scanner. The spiral sequence was compared against conventional Cartesian 4D flow (SENSE [sensitivity encoding] 2) in seven healthy volunteers and three patients (only spiral). In addition to comparing flow values, linear regression was used to assess internal consistency of aortic versus pulmonary ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…More recently, Petersson et al demonstrated that retrospectively gated intra-cardiac 4D flow MRI can be sped up without the use of acceleration techniques using respiratory navigated spiral trajectories. 26 This method does not compromise in spatio-temporal windows and demonstrates reliability and consistency for intra-cardiac flow quantification including diastolic inflow indices. However, mean scan times for spiral acquisition in their study were higher (13 6 3 min) than the most reliable acceleration technique in the present study, 4D-EPI (8 6 2 min), most likely because Petersson used respiratory navigation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…More recently, Petersson et al demonstrated that retrospectively gated intra-cardiac 4D flow MRI can be sped up without the use of acceleration techniques using respiratory navigated spiral trajectories. 26 This method does not compromise in spatio-temporal windows and demonstrates reliability and consistency for intra-cardiac flow quantification including diastolic inflow indices. However, mean scan times for spiral acquisition in their study were higher (13 6 3 min) than the most reliable acceleration technique in the present study, 4D-EPI (8 6 2 min), most likely because Petersson used respiratory navigation.…”
Section: Discussionmentioning
confidence: 93%
“…More recently, Petersson et al demonstrated that retrospectively gated intra‐cardiac 4D flow MRI can be sped up without the use of acceleration techniques using respiratory navigated spiral trajectories . This method does not compromise in spatio‐temporal windows and demonstrates reliability and consistency for intra‐cardiac flow quantification including diastolic inflow indices.…”
Section: Discussionmentioning
confidence: 98%
“…4D flow and 2D flow MRI data as well as morphological short‐axis and apical long‐axis cine images were acquired using a clinical 1.5T MRI scanner (Philips Achieva; Philips Medical Systems, Best, the Netherlands). The 4D flow data were acquired during free breathing using retrospectively ECG‐gated and navigator‐gated three‐dimensional, three‐directional phase contrast MRI (4D flow MRI) with asymmetric 4‐point motion‐encoding and either Cartesian or a stack of spiral readouts, as previously described . The Cartesian sequence scan parameters included: velocity encoding range (VENC) = 100 cm/s, flip angle 8°, echo time (TE) = 3.7 msec, repetition time (TR) = 6.3 msec, parallel imaging (SENSE) speed‐up factor = 2, field of view (FOV) = 230 × 230–274 × 274 mm 2 with a spatial resolution of 3 mm isotropic and an acquired temporal resolution of 49.2 msec.…”
Section: Methodsmentioning
confidence: 99%
“…Spiral MRI promises many benefits including high acquisition and SNR efficiency, short minimum echo‐times, robustness to motion and flow, and higher geometric fidelity (compared to EPI). In the past few years, spiral has been shown to provide unique capabilities or substantial advantages over conventional imaging in post‐Gad T 1 weighted imaging, 3D TSE imaging, cardiac flow imaging, diffusion weighted imaging, real‐time imaging, perfusion imaging, functional MRI, MR fingerprinting, and many other applications. Despite its potential and long history, spiral MRI has struggled to find widespread clinical adoption, in large part due to artifacts from susceptibility‐induced field inhomogeneity and eddy current‐induced gradient errors.…”
Section: Introductionmentioning
confidence: 99%